(untitled) (Research, Society and Development, 2020)
Immunoglobulin Y (IgY), a term used to refer to the main serum antibody in chickens and present in large quantities in egg yolks, has been shown to be highly relevant in scientific circles in recent decades. Recent studies have advanced when studying the relationship of immunoglobulin with antimicrobial and antibiofilm actions. Therefore, the aim of the present study is to analyze structural and functional aspects of immunoglobulin Y as well as its antimicrobial and antibiofilm activity. For this, a search was performed in the PubMed / MEDLINE, Cochrane and EMBASE databases, using the MeSH / DeCS descriptors “Dental caries”, “IgY” and their derivates, associated with each other by the Boolean operator “AND” and adapted for each data base. In addition, a complementary search was made on Google Scholar and on the references of selected articles. After a critical reading of titles and abstracts, 10 studies were selected. The review includes studies published in the past 20 years. In addition to having a potential use in dental treatments, immunoglobulin Y was shown to be efficient in reducing pathogens such as Salmonella spp and Pseudomonas aeruginosa. In the oral cavity, immunoglobulin showed a selective actio of bacteria Streptococcus mutans. However, there is no consensus in the literature about the action of IgY in candidiasis, nutritional and metabolic diseases. Therefore, immunoglobulin Y has a good antimicrobial action in vitro and in vivo in biofilm bacteria, but further studies are needed in order to elucidate its action against other bacteria and its clinical applicability.